Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To do substitutions, you take a phrase equal to one letter and you put that phrase in the other equation. The equations we're working with are
y = 6x - 11
-2x - 3y = -7
So it's already set up for us: it gives us what y equals; 6x - 11. So, just plug 6x - 11 into the y of the other equation
-2x - 3(6x - 11) = -7 Then you distribute the -3 on the outside of the parentheses to the 6x and the -11 on the inside.
-2x - 18x + 33 = -7 Move a few numbers around and add like terms.
-20x = -40 Then, just solve for x by dividing by -20.
x = 2
So, now you have the x: 2. Use that to find the y in y = 6x-11 by plugging in the 2 for the x.
y = 6(2) - 11
y = 12 - 11
y = 1
So, the answer is x = 2 and y = 1, or the ordered pair (2, 1)
y = 6x - 11
-2x - 3y = -7
So it's already set up for us: it gives us what y equals; 6x - 11. So, just plug 6x - 11 into the y of the other equation
-2x - 3(6x - 11) = -7 Then you distribute the -3 on the outside of the parentheses to the 6x and the -11 on the inside.
-2x - 18x + 33 = -7 Move a few numbers around and add like terms.
-20x = -40 Then, just solve for x by dividing by -20.
x = 2
So, now you have the x: 2. Use that to find the y in y = 6x-11 by plugging in the 2 for the x.
y = 6(2) - 11
y = 12 - 11
y = 1
So, the answer is x = 2 and y = 1, or the ordered pair (2, 1)
y=6x-11 (label equation 1)
-2x-3y=-7 (label equation 2)
sub 1 into 2
-2x-3(6x-11)=-7
-2x-18x+33=-7 (i expanded the brackets)
-20x+33=-7 (i simplified by adding like terms)
-20x=-40 (i subtracted 33 to both sides)
x=2 (i divided by -20 to both sides)
sub x=2 into 1
y=6(2)-11
y=12-11
y=1
therefore x=2 and y=1
-2x-3y=-7 (label equation 2)
sub 1 into 2
-2x-3(6x-11)=-7
-2x-18x+33=-7 (i expanded the brackets)
-20x+33=-7 (i simplified by adding like terms)
-20x=-40 (i subtracted 33 to both sides)
x=2 (i divided by -20 to both sides)
sub x=2 into 1
y=6(2)-11
y=12-11
y=1
therefore x=2 and y=1
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.